Sewage Water Treatment by Electrocoagulation Process - Mohd, Nasrullah; Zularisam, A. W.; Fadzil, Mat Yahaya (Penerbit UMP, 2012)
Treatment of wastewater from sewage water by electrocoagulation (EC) was investigated. Experiments were conducted to determine the optimum operating conditions such as electrode type, pH, current density and operation time. Aluminium and mild steel electrodes were used, and aluminium electrodes were found to be more suitable since it had a higher removal rate of Chemical Oxygen Demand (COD), Biochemical Oxygen Demand (BOD) and Suspended Solids (SS) than the mild steel electrode. The removal efficiencies of COD and BOD and SS were high, being 92.5%, 91.5% and 90.5%, respectively, with retention time 60 minutes. pH range between 3 to 11 was investigated during EC process and the optimum condition for pH was 7. Low current densities of 4.17 mA/cm2 , 8.33 mA/cm2 , 12.5 mA/cm2, 20.83 mA/cm2 and 25 mA/cm2 have been used in this experiment and the optimum current density of 25 mA/cm2 was obtained.